2021
DOI: 10.1038/s41598-021-96849-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation entrains alpha oscillatory activity in occipital cortex

Abstract: Parieto-occipital alpha rhythms (8–12 Hz) underlie cortical excitability and influence visual performance. Whether the synchrony of intrinsic alpha rhythms in the occipital cortex can be entrained by transcranial magnetic stimulation (TMS) is an open question. We applied 4-pulse, 10-Hz rhythmic TMS to entrain intrinsic alpha oscillators targeting right V1/V2, and tested four predictions with concurrent electroencephalogram (EEG): (1) progressive enhancement of entrainment across time windows, (2) output freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 106 publications
(131 reference statements)
0
17
1
Order By: Relevance
“…Going forward, additional criteria may be needed to establish whether entrainment took place. For example, an entrained oscillator should reverberate for a number of cycles after the cessation of its external drive (Barne et al, 2021, this issue;Lakatos et al, 2013;Lin, Shukla, et al, 2021;van Bree et al, 2021).…”
Section: Interim Discussionmentioning
confidence: 99%
“…Going forward, additional criteria may be needed to establish whether entrainment took place. For example, an entrained oscillator should reverberate for a number of cycles after the cessation of its external drive (Barne et al, 2021, this issue;Lakatos et al, 2013;Lin, Shukla, et al, 2021;van Bree et al, 2021).…”
Section: Interim Discussionmentioning
confidence: 99%
“…Frequencies distributed across a large number of frequency bins characterize unpredictable signals featuring higher entropy levels. This is in contrast with the synchronization of local oscillators at a single regular frequency during alpha or high-beta stimulation (Lin et al, 2021;Stengel et al, 2021;Thut et al, 2011a;Vernet et al, 2019) which gives rise to regular and predictable oscillating signals of very low entropy, within a single and narrow power peak. In this framework, EEG recordings in the present study showed that, compared to rhythmic bursts, the delivery of non frequency-specific TMS to the left frontal cortex resulted in higher levels of signal entropy, hence higher levels of neural noise.…”
Section: Discussionmentioning
confidence: 81%
“…While the cells and mechanisms through which PFC brain stimulation can reduce alcohol cravings remain unresolved, we propose that cortical INs represent compelling candidates. TMS modifies neural circuits through repetitive rhythmic stimulations thought to entrain oscillatory activities (Lin et al, 2021 ). In addition, the long-term efficacy of brain stimulation approaches is thought to be related to persistent effects on synaptic plasticity (Hanlon et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%